A preclinical model of peripheral T‐cell lymphoma GATA3 reveals DNA damage response pathway vulnerability - Elizabeth A Kuczynski; Giulia Morlino; Alison Peter; Anna M L Coenen‐Stass; Jennifer I Moss; Neha Wali; Oona Delpuech; Avinash Reddy; Anisha Solanki; Charles Sinclair; Dinis P Calado; Larissa S Carnevalli (EMBO Molecular Medicine)
Abstract Peripheral T‐cell lymphoma (PTCL) represents a rare group of heterogeneous diseases in urgent need of effective treatments. A scarcity of disease‐relevant preclinical models hinders research advances. Here, we isolated a novel mouse (m)PTCL by serially transplanting a lymphoma from a germinal center B‐cell hyperplasia model (Cγ1‐Cre Blimp1fl/fl) through immune‐competent mice. Lymphoma cells were identified as clonal TCRβ+ T‐helper cells expressing T‐follicular helper markers. We also observed coincident B‐cell activation and development of a de novo B‐cell lymphoma in the model, reminiscent of B‐cell activation/lymphomagenesis found in human PTCL. Molecular profiling linked the mPTCL to the high‐risk “GATA3” subtype of PTCL, showing GATA3 and Th2 gene expression, PI3K/mTOR pathway enrichment, hyperactivated MYC, and genome instability. Exome sequencing identified a human‐relevant oncogenic β‐catenin mutation possibly involved in T‐cell lymphomagenesis. Prolonged treatment responses were achieved in vivo by targeting ATR in the DNA damage response (DDR), a result corroborated in PTCL cell lines. This work provides mechanistic insight into the molecular and immunological drivers of T‐cell lymphomagenesis and proposes DDR inhibition as an effective and readily translatable therapy in PTCL.